The effect of teamwork on personnel’s job satisfaction and an application - Bulut, Elvan (My University, 2004)
Name and Surname: Elvan BULUT Field: Public Administration Programme:Human Resources Management and Development Supervisor: Professor Nevin DENİZ Degree Awarded and Date: Master- October 2004 Teamwork, Job Satisfaction

THE EFFECT OF TEAMWORK ON PERSONNEL'S JOB SATISFACTION By the changes of economic and social environment during the 1990's ocular variations at structure and management of organizations have taken the stage. One of these variations is the increased application of teamwork at organizations. Organizations have realized that teamwork helps organizations to prove their existence toward their rivals. Since, teamwork supports decision making, helps to solve problems via collectivity, increases employees' motivation, goes beyond the hierarchical structure of organizations that are stiff and unnecessary and etc. All of these factors are the basic reasons for the popularity of teamwork during the recent years. The most significant point that has been tried to be underlined in this study is the link between teamwork and job satisfaction. This study tries to depict that teamwork has a positive impact on personnel's job satisfaction. Employees' job satisfaction is increased when they work in teams. Via working in teams, employees' satisfaction has increased due to the fact that working collectively makes them to share their responsibilities, to create many kinds of ideas on a specific issue, to decrease their work load, not to feel loneliness within their tasks, and etc. Thus, they become automatically satisfied. Soyadı: Elvan BULUT Kamu Yönetimi Human Resources Management and Development Prof. Dr. Nevin DENİZ Tez Türü ve Tarihi: Yüksek Lisans- Ekim 2004 Teamwork, Job Satisfaction ÖZET TAKIM ÇALIŞMASININ PERSONELİN İŞ TATMİNİNE ETKİSİ 1990'larda organizasyonların yapı ve yönetimleri ekonomik ve sosyal çevrede ki değişimlerden ötürü çeşitlenmeye başlamıştır. Bu değişimlerden bir tanesi, organizasyonlarda takım çalışmasının artan kullanımıdır. Organizasyonlar, bünyelerinde sıklıkla üzerinde durdukları takım çalışmasının rakiplerinin karşısında durmalarına yardımcı olduğunu fark ettiler. Bunun sebebi, takım çalışması karar alma sürecini kolaylaştırmakta, elbirliği ile problemleri çözmeye yardımcı olmakta, çalışanların motivasyonunu yükseltmekte, örgütlerin katı ve gereksiz hiyerarşik yapısının ötesine geçerek çalışana hareket alanı bırakmakta, vb. Tüm bu faktörler takım çalışmasının son yıllarda ki popülerliğinin temel nedenlerindendir. Bu çalışmada altı çizilen asıl önemli nokta ise, takım çalışması ve iş tatmini arasındaki bağlantıdır. Bu çalışmayla takım çalışması ve iş tatmini arasındaki ilişki anlatılmaya çalışılmıştır. Takım çalışmasına iştirak etmeleriyle çalışanların iş tatmini düzeyleri yükselmektedir. Takım halinde çalışarak personelin iş tatmini yükselmektedir çünkü personel takım halinde çalışarak sorumluluklarını paylaşmış olurlar, bir tek konu hakkında birçok değişik fikir üretebilirler, iş yüklerini azaltabilirler, yapmaları gereken iş içinde kendilerini yalnız hissetmezler, vb. Böylelikle, çalışanlar direkt olarak tatmin olmuş olurlar.
Keywords: Ekip Çalışması; İş Tatmini